Adverse association of epicardial adipose tissue accumulation with cardiac function and atrioventricular coupling in postmenopausal women assessed by cardiac magnetic resonance imaging - Huang, Shan; Shi, Ke; Jiang, Li; Ren, Yan; Wang, Jin; Yan, Wei-Feng; Qian, Wen-Lei; Li, Yuan; Yang, Zhi-Gang (Frontiers in Cardiovascular Medicine, 2022)
Background This study aims to investigate the association of epicardial adipose tissue (EAT) accumulation with cardiac function and atrioventricular coupling in a cohort of postmenopausal women assessed by cardiac magnetic resonance imaging (CMR). Methods Overall, 283 postmenopausal women (mean age 61.5±9.1 years) without overt cardiac dysfunction, who underwent CMR examination were enrolled. Participants were classified into four groups by the quartile of EAT volume. EAT volume was quantified on short-axis cine stacks covering the entire epicardium. CMR-derived cardiac structure and function, including left atrial (LA)- volume, emptying fraction, deformation, and left ventricular (LV)- mass, volume, ejection fraction, and deformation were compared among the four groups of graded EAT volume. Results LV mass (LVM) and LV remodeling index were both increased in the group with the highest EAT volume, compared to those in the lowest quartile (p = 0.016 and p = 0.003). The LV global longitudinal strain (GLS), LA- reservoir strain (RS), conduit strain (CS), and booster strain (BS), were all progressively decreased from the lowest quartile of EAT volume to the highest. Multivariable linear regression analyses showed that EAT was independently associated with LVM, LV-GLS, LA-RS, LA-CS, and LA-BS after adjusting for age, systolic blood pressure, heart rate, hypertension, diabetes, dyslipidemia, menopausal age, and body mass index. Conclusion EAT accumulation is independently associated with subclinical LV and LA function in postmenopausal women without overt cardiovascular diseases. These associations support the role of EAT in mediating deleterious effects on cardiac structure and function.